Factors associated with patient satisfaction with foot and ankle surgery in a large prospective study - Dawson, J; Boller, I; Doll, H; Lavis, G; Sharp, R; Cooke, P; Jenkinson, C (2012)
Background: There is minimal published research on outcomes and satisfaction with foot and ankle surgery. Objective: To investigate patient-reported outcomes and satisfaction, and investigate which factors influence satisfaction at 9 months following foot or ankle surgery. Methods: Prospective study of 671 adult patients having foot or ankle surgery. Pre-and post-surgery, patients self-completed MOXFQ, SF-36 and EQ-5D questionnaires. Using ratings to a satisfaction item, patients who were 'very pleased' with the outcome were compared with everyone else, using multiple logistic regression, regarding their pre-, peri- and post-operative characteristics. Results: Of 628 eligible patients, 491 (73%) completed pre-and post-operative questionnaires. Following adjustment, satisfaction with surgery was influenced by patients' perceptions of their foot/ankle's appearance (OR 0.12, 95% CIs 0.06-0.23, p<0.001); wearable range of shoes (OR 0.36, 95% CIs 0.17-0.79, p=0.01); continued foot/ankle pain (OR 0.06, 95% CIs 0.03-0.14, p<0.001); impairment in Social-Interaction (MOXFQ SI scale) (OR 0.98, 95% CIs 0.96-0.99, p=0.009). The final explanatory model explained 67% of the variance in patient satisfaction. Conclusions: Foot appearance, wearable shoe range, the (full) alleviation of pain and the ability/confidence to interact socially are crucial to peoples' satisfaction with their foot or ankle surgery. © 2012 Elsevier Ltd.